Diabetes-specific quality of life scale (DSQOL): Translation and validation of Urdu short version - Laraib Javaid; Nasreen Akhtar; Iffat Batool; Muhammad Zohaib khan (Journal of University Medical & Dental College, 2023)
ABSTRACTBACKGROUND & OBJECTIVE: Quality of life has been affected by numerous psychosocial factors. Thus, for diabetic patients, it was necessary to identify the underlying factors, keeping in view the cultural norms. The objective of the current study was to validate the cultural norms of DSQOL (Diabetes-Specific Quality of Life Scale) through translation into "Urdu" language.METHODOLOGY: A correlational research design was used in the study. Initially, the forward and backward translation method was followed to translate DSQOL. Afterward, the final Urdu translated version (20 items) was tested on a representative sample of 200 diabetic patients to establish its psychometric properties.RESULTS: Internal consistency and correlational matrix of original, Urdu, and English scales yielded reliable results. In the main study, 200 male and female diabetic patients with an age range of 30-70 years and an average of (M±SD;45±8.25) participated. The reliability analysis showed a significant alpha coefficient for five subscales; "Social relations (α= .80), Physical complaints (α=.90), Worries about the future (α= .88), Daily hassles (α= .88), and Emotional worries (α=.87)". The item analysis of Urdu version confirmed the item total correlation of all subscales except three items. Further, CFA confirmed the factor structure of the newly translated Urdu version of DSQOL through AMOS (Analysis of Moment Structure), and the model yielded acceptable model fit indices (CFI=.90; NFI= .90). The Final Urdu version of DSQOL had 20 items.CONCLUSION: The Urdu version of DSQOL is a valid and reliable measure for assessing the diabetics-specific quality of life. This translated tool overcame the cultural barrier with respect to language and norms.